ІТЕРАЦІЙНИЙ МЕТОД ВИЗНАЧЕННЯ ПАРАМЕТРІВ ПЕРЕТВОРЮВАЧІВ ДИФЕРЕНЦІЙНИХ КОНДУКТОМЕТРИЧНИХ СЕНСОРІВ - Борщов, П.І.; Мельник, В.Г. (Інститут електродинаміки НАН України, Київ, 2024)
The proposed method is a development of the well-known one, based on the determination of the sensor's transducers impedance parameters according to the three-element equivalent circuit at two frequencies. The increase in accuracy is achieved due to the step-by-step refinement of parameter values using the values obtained in the previous step using simplified mathematical expressions. Mathematical expressions for calculating the specified parameters are presented. Comparative results of calculations based on known and proposed methods using a computer model are presented, which showed the possibility of significantly reducing the influence of changes in the background electrical conductivity of the solution compared to the known method. References 9, figures 2, tables 1.